Absolute beginner's guide to Minecraft Mods programming : no experience necessary! - Cadenhead, Rogers (Absolute beginner's guide (Indianapolis, Ind.), 2016)
Now you can mod your Minecraft game environment into anything you can imagine, without becoming a technical expert! This book is the fastest way to master Minecraft modding and use Java to transform the Minecraft game's worlds, tools, behavior, weapons, structures, mobs ... everything! Plus, you'll learn Java programming skills you can use anywhere. Learn how to do what you want, the way you want, one incredibly easy step at a time. Modding the Minecraft game has never been this simple! --Publisher's description.